The effect of index option trading on stock market volatility in China: An empirical investigation - Kai Wu; Yi Liu; Weiyang Feng (Journal of Risk and Financial Management, 2022)
In this study, we examine the effect of introducing SSE 50ETF index options trading on stock market volatility using a panel data evaluation approach. Based on the cross-sectional dependence among international stock indices and macroeconomic indicators, we estimate the counterfactual volatility of the SSE 50 index and find that the introduction of index options reduces stock market volatility significantly in the long term. The primary findings are robust to alternative econometric models, including principal component analysis, GARCH-family model, and LASSO regression. The results of this paper suggest that the introduction of SSE index options provides investors with risk management tools and improves price discovery in the stock market.
Keywords: 330; stock market volatility; panel data; GARCH; counterfactual; LASSO